PEMBINAAN GURU HONORER SEKOLAH DASAR DI KABUPATEN SUMBA BARAT DAYA - Zasa, Marcelus Umbu; Poerwanti, Endang; Anshory, Ichsan (Jurnal Kebijakan dan Pengembangan Pendidikan, 2015)
Abstract: This study aims to (1) knowing the formation of honorary primary school teachers in Southwest Sumba District; (2) knowing the supporting and inhibiting factors of the formation of honorary primary school teachers in Southwest Sumba district. The design of this research is to use a descriptive qualitative approach. Data collection techniques were carried out through interviews with the Head of the education office, Superintendent of primary schools, Principals and regional honorary teachers to find a picture of the performance and training techniques of regional honorary teachers and documentation techniques to strengthen the research results presented in the form of photographs. The results showed that 1) Regional Honorary Teacher's performance was classified as good and the training technique was still not effective. 2) Factors that support the improvement of the performance and guidance of regional honorary teachers in the Southwest Sumba District are from the school supervisor, the principal of the primary school, to participate in the coaching program that is held. Availability of transportation budget. The obstacle that arises is the lack of understanding of interest, there are still regional honorary teachers who copy-paste learning tools, motivation, and attitudes of regional honorary teachers about the importance of coaching which is still low as well as the techniques of guiding regional honorary teachers that have not been effective.Keywords: Coaching, Performance, Honorary Teacher Abstrak: Tujuan penelitian ini yaitu untuk (1) mengetahui pembinaan guru honorer sekolah dasar di Kabupaten Sumba Barat Daya; (2) mengetahui faktor pendukung dan penghambat pembinaan guru honorer sekolah dasar di Kabupaten Sumba Barat Daya. Desain penelitian ini yaitu mengunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data dilakukan melalui wawancara bersama Kepala dinas pendidikan, Pengawas sekolah dasar, Kepala sekolah dan guru honorer daerah untuk mengetahui gambaran kinerja dan teknik pembinaan guru honorer daerah dan teknik dokumentasi untuk memperkuat hasil penelitian yang dipaparkan dalam bentuk foto. Hasil penelitian menunjukkan1) Kinerja Guru Honorer Daerah tergolong baik dan teknik pembinaan yang masih belum efektif. 2) Faktor-faktor yang mendukung peningkatan kinerja dan pembinaan guru honorer daerah di kabupaten sumba barat daya adalah dari pengawas sekolah, Kepala sekolah dasar, untuk mengikuti program pembinaan yang diadakan. Tersedianya anggaran transportasi. Kendala yang muncul adalah kurangnya pemahaman minat, masih adanya guru honorer daerah yang mengkopi paste perangkat pembelajaran, motivasi dan sikap guru honorer daerah tentang pentingnya pembinaan yang masih rendah serta teknik pembinaan guru honorer daerah yang belum efektif.Kata kunci: Pembinaan, Kinerja, Guru honorer